UI/UX design of a digital library using figma (case study: high school) - Putri, Ranti Eka; Fadly, Yossy; Purwanto, Dedi; Pardede, Jatua (Jurnal Mandiri IT, 2024)
This research focuses on the development of UI/UX design for a web-based digital library specifically designed for high school students, using the Figma application as the primary tool. Digital libraries are essential for providing quick and easy access to educational resources; however, many platforms still lack user-friendly interfaces and can be difficult to navigate, which may limit students' access to learning materials. By adopting a simpler, more responsive, and intuitive UI/UX design approach, students are expected to better utilize digital libraries, thereby enhancing their motivation to learn. Figma enables a more collaborative and efficient design process, allowing designs to be tested and refined according to user needs. Through this research, the digital library is expected to become a more engaging and accessible learning resource, while contributing to improved interface design innovation in the digital education sphere.